MADS-box transcription factors MADS11 and DAL1 interact to mediate the vegetative-to-reproductive transition in pine. Issue 1 (29th May 2021) - Ma, Jing-Jing; Chen, Xi; Song, Yi-Tong; Zhang, Gui-Fang; Zhou, Xian-Qing; Que, Shu-Peng; Mao, Fei; Pervaiz, Tariq; Lin, Jin-Xing; Li, Yue; Li, Wei; Wu, Harry X.; et al.
Abstract: The reproductive transition is an important event that is crucial for plant survival and reproduction. Relative to the thorough understanding of the vegetative phase transition in angiosperms, a little is known about this process in perennial conifers. To gain insight into the molecular basis of the regulatory mechanism in conifers, we used temporal dynamic transcriptome analysis with samples from seven different ages of Pinus tabuliformis to identify a gene module substantially associated with aging. The results first demonstrated that the phase change in P. tabuliformis occurred as an unexpectedly rapid transition rather than a slow, gradual progression. The age-related gene module contains 33 transcription factors and was enriched in genes that belong to the MADS (MCMl, AGAMOUS, DEFICIENS, SRF)-box family, including six SOC1-like genes and DAL1 and DAL10 . Expression analysis in P. tabuliformis and a late-cone-setting P. bungeana mutant showed a tight association between PtMADS11 and reproductive competence. We then confirmed that MADS11 and DAL1 coordinate the aging pathway through physical interaction. Overexpression of PtMADS11 and PtDAL1 partially rescued the flowering of 35S::miR156A and spl1, 2, 3, 4, 5, 6 mutants in Arabidopsis ( Arabidopsis thaliana ), but only PtMADS11 could rescue the flowering of the ft-10 mutant, suggesting PtMADS11 and PtDAL1 play different roles in flowering regulatory networks in Arabidopsis. The PtMADS11 could not alter the flowering phenotype of soc1-1-2, indicating it may function differently from AtSOC1 in Arabidopsis. In this study, we identified the MADS11 gene in pine as a regulatory mediator of the juvenile-to-adult transition with functions differentiated from the angiosperm SOC1 . Abstract : As an age biomarker, the MADS transcription factor DAL1 interacts with a strict maturity-related MADS transcription factor to mediate the vegetative-to-reproductive transition in pine.